LINK BETWEEN EARLY CHILDHOOD CARIES AND STUNTING: A PUBLIC HEALTH PERSPECTIVE - Ameliana, Yemy; Fauziah, Yessy Andriani; Darmadi, Eveline Yulia; Setianingtyas, Dwi (HEARTY, 2025)
Early childhood caries and stunting are two major health issues that often coexist, particularly in developing countries. Both conditions have long-term impacts on children's growth, development, and overall quality of life. This literature review aims to explore the association between early childhood care and development (ECC) and stunting from a public health perspective. The method employed was a narrative review of scientific articles sourced from PubMed, Scopus, and Google Scholar databases from 2017 to 2024. The findings indicate a strong correlation between poor nutritional status and a high incidence of early childhood caries among preschool-aged children. Shared risk factors such as unhealthy dietary patterns, low parental health literacy, and limited access to dental care services further reinforce this link. The review emphasizes the importance of an integrated, promotive, and preventive approach that combines nutrition and oral health interventions within public health programs. Integrating oral health services into stunting prevention strategies at the community level is considered essential for improving children's overall health outcomes.